The Integrated Use of Dendrochronological Data and Paleoecological Records From Northwest European Peatlands and Lakes for Understanding Long-Term Ecological and Climatic Changes—A Review - Edvardsson, Johannes; Helama, Samuli; Rundgren, Mats; Nielsen, Anne Birgitte (Frontiers in Ecology and Evolution, 2022)
Our overall understanding of long-term climate dynamics is largely based on proxy data generated from archives such as ice cores, ocean sediments, tree rings, speleothems, and corals, whereas reconstructions of long-term changes in vegetation and associated climate during the Holocene are largely based on palaeoecological records from peat and lake sequences, primarily pollen and plant macrofossil data. However, since no proxy can provide a complete picture of the past, it is important to integrate different types of data, and to use methods that can support the palaeoecological and palaeoclimatic interpretations. Here we review how tree-ring data and dendrochronological approaches can be integrated with stratigraphic records to provide complementary palaeoecological and palaeoclimatic information. The review includes multiproxy studies in which dendrochronological data have been either compared or integrated with stratigraphic records, mainly pollen records, with the aim to contribute to a better understanding of long-term ecosystem and climate dynamics. We mainly focus on studies from northwest Europe in which tree-ring data and at least one type of palaeoecological proxy record from the same site or area has been either compared or integrated. We find that integration of dendrochronological data and palaeoecological records from peat and lake sequences is a powerful but underutilized approach to reconstruct long-term ecological and climatic changes. One likely reason for its limited use is the contrasting character of the two categories of data, including their different time resolution and occurrence, making them difficult to integrate. For example, subfossil wood providing annual dendrochronological data usually only occurs sporadically in peat and lake sediments, and the presence/absence of the trees are normally expected to be recorded in the pollen data with multi-decadal or coarser resolution. Therefore, we also discuss methods to compare and integrate dendrochronological and stratigraphic records, as well as the relevant palaeoecological and palaeoclimatic information provided by dendrochronology, pollen, and peat stratigraphy, with the aim to facilitate new multi-proxy initiatives that will contribute to a better understanding of long-term ecosystem and climate dynamics and thereby a firmer basis for future nature conservation initiatives.